2021
DOI: 10.1051/e3sconf/202128203020
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic studies for common invasive and infectious pathologies of rabbits in the Orenburg region

Abstract: Rabbits, like other animal species, are susceptible to infection with invasive and infectious diseases. Both ecto- and endoparasites are registered in them, including helminths, insects on the body, acarus scabies, protozoa. Rabbits are characterized by a high degree of precocity, high fecundity and the breadth of use of the products obtained from them. As a product of rabbit breeding, first, meat is in demand as a dietary product. Part of the products from rabbits - hair, wool-molt is obtained during the life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Similar pathomorphological changes in the intestines are described by Z.K. Terentyeva et al (2021), who indicated serous-catarrhal and catarrhal-necrotic inflammations of the large intestine. Mesenteric lymph nodes are enlarged, hyperaemic, swollen.…”
Section: Figure 6 Fasting Intestine Of a Rabbit With Passalurosis: 1 ...supporting
confidence: 80%
See 2 more Smart Citations
“…Similar pathomorphological changes in the intestines are described by Z.K. Terentyeva et al (2021), who indicated serous-catarrhal and catarrhal-necrotic inflammations of the large intestine. Mesenteric lymph nodes are enlarged, hyperaemic, swollen.…”
Section: Figure 6 Fasting Intestine Of a Rabbit With Passalurosis: 1 ...supporting
confidence: 80%
“…Mykhailoutenko et al (2019) described pathomorphological changes in rabbits during the chronic course of passalurosis, i.e., with low II; Z.K. Terentyeva et al (2021) described these changes for medium and high II, where the main structural changes were revealed only in the large intestine of rabbits.…”
Section: Figure 6 Fasting Intestine Of a Rabbit With Passalurosis: 1 ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Its distribution, according to Z.K. Terentyeva et al (2021) is contributed by the unsanitary conditions of keeping rabbits on unchanged bedding or floors. The optimal air temperature for egg development, according to V. Yevstafieva et al (2021Yevstafieva et al ( , 2022 is +35°C.…”
Section: Introductionmentioning
confidence: 99%